Co-pyrolysis of mild liquefaction solid product and low rank coals: Products distributions, products properties and interactions. (15th December 2021) - Feng, Zhihao; Bai, Zongqing; Hou, Ranran; Guo, Zhenxing; Kong, Lingxue; Bai, Jin; Li, Wen
Graphical abstract: Highlights: Hydrogen supply and mass transfer inhibition simultaneously exist in co-pyrolysis. Two bonding processes of MLS and LRC in co-pyrolysis are proposed. The addition of LRCs could reduce the aromaticity of co-pyrolysis tar. Abstract: Co-pyrolysis of Hami coal mild liquefaction solid product (MLS) and two low rank coals (LRCs), Hami coal (HM) and Hefeng coal (HF) with different blending ratios were conducted on a fixed-bed reactor. The products distributions, gas emission characteristics and product properties during co-pyrolysis were synthetically analyzed by multiple methods, which are conducive to understanding the co-pyrolysis interactions. Results show that two effects simultaneously exist in the co-pyrolysis process. As LRCs ratio is high, the effect of hydrogen supply from LRCs to the volatile free radicals is dominant, resulting in more volatiles being stabilized and lower gas yield. While on the other, as LRCs ratio is low, the mass transfer inhibition caused by the softening and melting of MLS is dominant. This makes it difficult for the volatiles produced during co-pyrolysis to escape from the sample system and intensifying the secondary reactions, which leads to the increase of char yield and decrease of volatile yield. The bonding process of MLS and LRCs during co-pyrolysis is significantly affected by the sample blending ratio. Compared with the chemical and pore structures, AAEMs play a more significant catalytic role on the gasification reactivity of the co-pyrolysis char. Furthermore, the addition of LRCs could reduce the aromaticity of co-pyrolysis tar, increase the substitution degrees of aromatic rings and content of olefin.